Andreas Gross an einer Veranstaltung zu Stop F/A-18
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Friedensbewegung politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Pazifismus Sicherheitspolitik;Verteidigung;Armee;Armeeabschaffung;GSoA